A preliminary assessment of the LMA protector™ in non-paralysed patients. Issue 1 (December 2017) - Sng, Ban; Ithnin, Farida; Mathur, Deepak; Lew, Eileen; Han, Nian-Lin; Sia, Alex
Abstract Background The LMA Protector™ is the latest CE marked single use supraglottic airway device. This airway device provides access and functional separation of the respiratory and digestive tracts. There are two ports (male, female ports) to provide suction in the laryngeal region and insertion of the gastric tube. The aim of our study is to assess the ease of use, airway quality, device positioning, airway leak and complications associated with initial clinical experience in LMA Protector™ usage. Methods This is an initial investigation of LMA Protector™ airway device. We conducted a preliminary assessment in the anaesthetised women who underwent minor gynaecological procedures with spontaneous ventilation in order to evaluate the performance of the airway device. Results Insertion was successful on first and second attempts in 23 (88.5%) and 3 (11.5%) respectively. Median [IQR (range)] insertion time was 19 [17-21(14-58)] seconds. Airway leak pressure was 25.5 [23-29(21-30] cmH2 O. On fibreoptic examination via the device, vocal cords were visible in all 26 patients. There were no alternative airway use or airway manipulations required during maintenance of anaesthesia. Six patients had sore throat 24 h after procedures and there was no dysphagia or hoarseness. Conclusion This pilot study of the LMA protector shows that the device is easily inserted with fast insertion time, providing a reliable and adequate airway seal. Trial registration Clinicaltrials.gov RegistrationNCT02531256 . Retrospectively registered on August 21, 2015.